The practice and challenges of solid waste management in Damaturu, Yobe State, Nigeria - Babalola, Ayo (Scientific Research, 2010)

(untitled)
This paper presents an overview of the current solid waste management practices in Damaturu town and provides a brief discussion on the future challenges. Damaturu town became a state capital in August 1991. Since then the population has been on a steady increase mainly due to influx of people and its strategic location along axial route to major cities in the northeast region. Wastes are being generated mainly from residential, commercial and institutional land uses. Waste collection bins are placed at strategic locations identified by the agency and termed as high waste generating points with wheeled plastic waste bins, metal waste bins and constructed waste bunkers. The contents of these bins are finally disposed of at a location 6 kilometers away from the generating points. Spatial data on waste distribution was collected using a global positioning system (GPS). The data was manipulated and processed using Geographic information system (GIS) to produce the waste distribution map. Findings revealed that the existing solid waste management system is inefficient as the present practice rely on monthly collection and disposal of waste using an open dump site.